Pengaruh Realisasi Biaya Operasional dan Beban Pokok Pendapatan terhadap Jasa Pemanduan Kapal pada PT Penajam Internasional Terminal Periode 2020-2024 - Sherlita Christanta Saragih; Afrizawati Afrizawati; Claudya Nurcahaya (Jurnal Riset dan Inovasi Manajemen, 2026)
This study aims to analyze the effect of the realization of operating costs and cost of revenue on ship pilotage services at PT Penajam Internasional Terminal during the 2020–2024 period. The study is motivated by fluctuations in ship pilotage services, which are suspected to be associated with changes in the realization of the company’s operating costs and cost of revenue. This study employs a quantitative approach with a descriptive method. The data used are secondary data obtained from the financial statements of PT Penajam Internasional Terminal for the 2020–2024 period through documentation and supported by interviews. The population and sample consist of five annual financial statements, determined using a saturated sampling technique. Data analysis was conducted using multiple linear regression with IBM SPSS Statistics. The results show that the realization of operating costs has a positive regression coefficient of 2.282 but does not have a significant effect on ship pilotage services, with a significance value of 0.078 > 0.05. The realization of the cost of revenue also has a positive regression coefficient of 0.873 but does not have a significant effect on ship pilotage services, with a significance value of 0.095 > 0.05. Simultaneously, the two variables also do not have a significant effect on ship pilotage services, with a significance value of 0.136 > 0.05. Nevertheless, the research model is able to explain 86.4% of the variation in ship pilotage services, while the remaining 13.6% is influenced by other factors outside the research model.